The effect of co-regulation on English public speaking self-efficacy in collaborative oral presentations - Hao, Xia; Chen, Hua (Frontiers in Psychology, 2024)
This study investigated the influence of co-regulation on public speaking self-efficacy in the context of collaborative oral presentations. A total of 237 students enrolled in an English course at a university in China took part in the research. The factor analysis findings revealed that learners' co-regulation in public speaking encompass five components: co-planning, co-monitoring, co-evaluation, effort regulation, and help-seeking. Public speaking self-efficacy, on the other hand, pertains to learners' confidence in aspects including the topic, language use, organization, and delivery during public speaking engagements. The path analysis demonstrated that co-planning was a significant predictor of students' self-efficacy in terms of the topic and organization. Moreover, the co-monitoring strategy exhibited direct and positive correlations with language and topic self-efficacy. Similarly, the co-evaluation strategy showed direct and positive relationships with language, delivery, and organization self-efficacy. Furthermore, both effort regulation and help-seeking strategies were found to have direct and positive impacts on organization self-efficacy. This study offers valuable implications for educators, trainers, and individuals aiming to enhance their public speaking self-efficacy in collaborative environments.